Training on installing solar water pump for resident of singkar 1 wareng wonosari gunungkidul yogyakarta indonesia - Alfian Ma’arif; Khoirudin Wisnu Mahendra; Suko Ferbriyanto; Alfan Habibillah; Ahmad Nurimam (Peneliti Teknologi Teknik Indonesia, 2021)
Singkar 1 Hamlet, Wareng Village, Wonosari, Gunungkidul, Yogyakarta is a mountainous area that often experiences a shortage of clean water and does not yet have the technology to empower efficient irrigation. During the dry season, residents have to buy water from the Village Drinking Water Manager for daily needs and other needs such as watering plants. Geographical conditions that depend on seasonal changes are an obstacle in the availability of water irrigation facilities, but Dusun Singkar 1 Wareng has the potential to be developed because it has a large area of land and there are wells that have not been utilized for plant cultivation. The irrigation system works by draining water from residents' wells using a solar-powered DC water pump to irrigate land that has not been used optimally by residents. This system is able to increase the independence of residents in cultivating plants because residents can use water without having to buy it from the local village drinking water manager.